Armed Conflict and Health Risks as Long-term Impacts: A Global Humanitarian Issue - Purwanti, Sri (BKM Public Health and Community Medicine, 2024)
Purpose: Armed conflicts are public health emergencies that cause acute and chronic health impacts, including rapidly spreading infectious diseases and long-term non-communicable diseases. This literature review aims to identify health risks associated with conflicts in specific regions. Methods: This article is a literature review based on books, journals, and other references. Results: The study identified a skin leishmaniasis outbreak during the Syrian conflict. Tuberculosis incidence and prevalence doubled in conflict areas. Measles and hepatitis B outbreaks occurred rapidly among refugees in Yemen and Syria. Cholera outbreaks were reported in refugee camps in conflict zones in Yemen and Somalia, with water facility bombings in Yemen leading to a cholera outbreak affecting 500,000 people. Hepatitis B, often linked with refugee camps, caused maternal fatalities in northern Sudan and Ethiopia. Russian military attacks led to the closure of HIV/AIDS clinics in Kharkiv and Mariupol, increasing treatment discontinuation and mortality risks for HIV/AIDS patients. Conflicts weaken disease surveillance and control systems, impacting vaccination, sanitation, and drinking water provision, thus increasing the risk of sanitation-based diseases. Disease eradication efforts, such as for polio, have been successful in several countries except conflict zones like Nigeria, Syria, Congo, and Afghanistan. Geospatial analysis shows that stunting rates among children born near conflict areas are 2-9% higher than average. Prolonged armed conflict diverts more resources from health to warfare. Conclusion: Armed conflict fundamentally poses a health risk, leading to long-term impacts due to systemic failures in control and prevention programs. This necessitates attention as a significant humanitarian issue.